New Evidence on the Relationship Between Corporate Social Responsibility and the Use of Equity Capital - Benlemlih, Mohammed; Bitar, Mohammad; Erragragui, Elias; Peillex, Jonathan (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
In this paper, we study the reverse U-shaped relationship between Corporate Social Responsibility (CSR) and firms’ use of equity capital. Using a large sample of U.S. publicly listed companies, we provide strong evidence that CSR is positively associated with the use of equity capital when CSR practices are below a certain level. Once the CSR investment exceeds this level, the relationship between CSR and the equity financing becomes negative. Our findings are robust when we use the individual components of CSR, and several approaches to address endogeneity. Overall, our results enrich the debate about capital structure of high CSR firms and suggest that the CSR-capital structure relationship is more complex than what has been demonstrated in previous literature.